The Enhancement of 3 MHz Ultrasonic Echo Signal for Conversion Curve Development for Acoustic Impedance Estimation by Using Wavelet Transform - Prastika, Edo Bagus; Gunawan, Agus Indra; Bayu Dewantara, Bima Sena; Hozumi, Naohiro; Prianto, Chandra Edy (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
Ultrasonic technology has already been used for many applications. Most of them are mainly used for object measurement. Some techniques have been widely applied to particular measurement by utilizing a very specific component. In this research, the previous technique to develop a conversion curve to obtain the acoustic impedance of the target is adopted. Then, we propose a 3 MHz concave shaped ultrasonic transducer for measuring liquids and a confirmation is needed to confirm if the system used is correct. Therefore, several saline solutions which property has been known are used. A low voltage of 10 Volt pulse is used to trigger the transducer. The ultrasonic wave is then transmitted through the multilayered mediums, which is pure water, clear acrylic, and the target. The echo from the interface between the acrylic and the target is then received by the same transducer. Some parameters such as peak and RMS are used to develop the conversion curve. A peak detection and comparison between the original echo and the processed one by using Wavelet transform (UWT and DWT) is then performed. Some analysis of the echo signal by using multiresolution and time-frequency analysis is also proposed. The result obtained from the measurement is then compared to that from the theoretical calculation. Based on the result, in terms of developing the calibration graph, only the RMS value (UWT) which has the closest trend to the result of the calculation, with the mean percentage error of 0.65512%, which is the smallest value among all parameters.